HOMESCHOOLING: Sebuah Pendidikan Alternatif - Ismail, Muh. Ilyas (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
This article aims to examine the theoretical concept, classification, and the imple-mentation of homeschooling in Indonesia. The discussion of homeschooling was in the perspective of child development. The conclusion based on the theoretical concept describes that it was an educational form which was done independently by family, and the learning materials were choosen in accordance with the chil-dren need. The homeschooling classification forms was divided into two forms namely single home schooling which was conducted independently by parents in one family withought collaborating with aothers.Compound homeschooling was conducted by two or more families for certain activities, but the main activities re-main to be implemented by the respective parents. Homeschooling was an educa-tion for the children who performed at home and was specifically provided by a parent or a professional tutor. Homeschooling in practice was to move the school from the public area to a more private area, which was home.